Clinicopathological significance and prognostic values of claudin18.2 expression in solid tumors: a systematic review and meta-analysis - Park, Gyerim; Park, Se Jun; Kim, Younghoon (Frontiers in Oncology, 2024)
ObjectiveClaudin18.2 has been established as a putative therapeutic target in human solid malignancies. The aim of this study is to determine claudin18.2 expression as a clinicopathological and prognostic factor in human solid tumors through a systematic review and meta-analysis. Articles were systematically reviewed for studies that included the correlation between claudin18.2 expression and clinicopathological features and prognosis in solid tumors. Meta-analysis was conducted to estimate either odds ratio and 95% confidence intervals (CIs) of clinicopathological factors or hazard ratio and 95% CIs of survival outcomes for claudin18.2 expression in all available solid tumors.Results21 studies including 5,331 patients were identified. Overall proportion of claudin18.2 positivity was 29.7%. Analyses of clinicopathological features demonstrated that claudin18.2 positivity correlated with male predominance, lower T stage, more frequent MUC5AC positivity when all primary tumors included. In subgroup analysis, gastric cancer showed significant correlation between high claudin18.2 expression and frequent EBV infection, male predominance and lower T stage. In lung cancer, claudin18.2 expression was associated with favorable overall survival. However, analyses of survival outcomes in all solid tumors showed that claudin18.2 expression was not associated with overall survival and pooled disease-free survival, tumor-specific survival, progression-free survival and relapse-free survival.ConclusionsOur study emphasizes evaluation of claudin18.2 expression as a potential prognostic factor in lung adenocarcinoma and further exploration in other solid tumors as well.Systematic review registrationhttps://www.crd.york.ac.uk/prospero/, identifier CRD42023468651.